Chemical Composition and Sensory Profile of Sauerkraut from Different Cabbage Hybrids - Elena V. Yanchenko; Galina S. Volkova; Elena V. Kuksova; Ivan I. Virchenko; Aleksey V. Yanchenko; Elena M. Serba; Maria I. Ivanova (Техника и технология пищевых производств)
Fermented foods have a longer shelf life and higher nutritional value. Sauerkraut products depend on the quality of the raw material. Not every cabbage variety is suitable for processing. The present research objective was to test several cabbage hybrids for natural fermentation, microbiological parameters, and native sugar content after four months of storage. The study featured twelve new-generation white cabbage hybrids of Russian selection and sauerkraut foods. The experimental batches were stored for four months at –1–0°C. Fermentation occurred at 21°C and final pH ≤ 3.6. The sugar content and titratable acidity were measured by standard methods. The method of limiting dilutions was applied to determine the microbial count. The microbiological seeding process followed standard procedures. The highest content of total sugars before fermentation belonged to the late-ripening hybrids Prestizh F1 (5.92%), Gertsoginya F1 (5.82%), and Idillia F1 (5.28%), as well as to the late-ripening Atlant F1 (5.49%). The greatest sugar content was registered in Prestizh F1 (4.78%), Kontinent F1 (4.30%), and Gertsoginya F1 (4.07%). The mass fraction of titratable acids in terms of lactic acid averaged 1.04% for all the samples. The difference in the chemical composition depended on the hybrid and microbial count during fermentation. The lactic acid bacteria content was as high as 8.17×107 CFU/cm3 in Severyanka F1. All the samples were resistant to undesirable microflora, i.e., yeasts and molds. All the cabbage hybrids were suitable for fermentation even after four months of storage. Their own lactic microflora was sufficient for fermentation and traditional sensory properties.